Dwindling Ground Water Table: An Ecological Study of Southern Haryana - Sangwan, Vikramaditya (Ecological Questions, 2023)
The dwindling ground water level is one of the critical issues that plague India in the present times. This research study primarily has its basis in the secondary data, gathered from the Ministry of Water Resources. The main aim of the present research study is to highlight the issues related to ground water in various parts of India with the main focus on southern part of Haryana state. The spatial pattern of the ground water depth is studied using the secondary data from various sources. The water table depth and fluctuation maps in Arch GIS 9.3 are analysed by making use of geological analysis extension. The water elevation is examined by employing the Kriging estimator. Also, the different ways of prevention that can help in checking the quick dwindling of ground water table are discussed so that the sustainable use of ground water can be encouraged and achieved. It is observed that the menace of ground water depletion has posed alarming threat to the states of Punjab, Haryana, Uttar Pradesh and some south Indian states. This is attributed mainly to the agricultural, industrial and human needs amidst the ever-rising rate of population in India. In the southern Haryana, the Mahendergarh district and Firozpur block of Mewat area have been identified as most critical zones in relation to water depletion. The study suggests judicious and sustainable use of water resources so as to check the alarming dwindling of the ground water table.